Abnormal Frenal Attachment and Analysis of Orthodntists Considerations of Determining but Over Looked Element - Kumari, Neelam; Joneja, Purva; Pereira Kalia, Ulrika Diana; Mishra, Samvit; Faraz, Sameen (Journal of Neonatal Surgery, 2025)
background and objectives: the aim of this study was to analyse the current clinical views of orthodontists on the periodontal impact of abnormal frenal attachments on various malocclusions and to gather the views of orthodontists, pan india on the management of abnormal frenal attachment., material and method: - a questionnaire containing 15 statements was sent to orthodontists all over india. the questionnaire covered demographics, orthodontists’ experience, questions regarding abnormal frenal attachments, its occurrence in various syndromes and questions regarding its management. results-. a hundred orthodontists with a range of backgrounds and experiences were chosen for this study. it was found that the choice of surgical intervention to correct midline diastema depended on the amount of midline diastema. 86% thought that papilla and papillary penetrating frenum was potentially pathological. 67% were able to link aberrant frenal attachments to syndromes such as holoprosencephaly and ellis-van creveld syndrome (evcs). 83% agreed on the blanch test as their test of choice to diagnose abnormal frenal attachments. 79 % of the orthodontists chose to check buccal tie by visual inspection but the correct method to diagnose this is by palpation or finger sweep. mostly all orthodontists agreed on the negative effects of abnormal labial frenal attachment, timing of frenectomy and that retention should include both bonded and removable retainers. conclusion- the following study was conducted to gather the current clinical views of orthodontists in india regarding the periodontal impact of abnormal frenal attachments on various malocclusions. although most of the orthodontists agreed that if the diastema was large and frenal attachments are thick, it may not be possible to completely close the space before surgical intervention. the space could be closed partially, followed by surgical intervention and orthodontic movement to bring the teeth together should resume immediately after the frenectomy. this is done so that the teeth are brought together quickly after the procedure. this causes the healing to occur with the teeth together which would result in the post-surgical scar tissue stabilizing the teeth instead of creating obstacles to final closure of the space